Analisis Kemiskinan Keluarga Nelayan Suku Bajo - Suryani Suryani; Rosmini Maru; Sukri Nyompa; Hasriyanti Hasriyanti; Amal Arfan; Saiful Hardiyansyah (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2026)
Poverty is a multidimensional condition influenced by various factors, such as economic, educational, health, and socio-cultural conditions. This study aims to describe the characteristics of poverty among the Bajo fishing community in Lamanggau Village. The research method used is descriptive qualitative through interviews and direct observation, as well as quantitative data support from survey results. The results show that the poverty of the Bajo fishing community is influenced by low levels of education, where the majority of heads of families only completed elementary school. Low education has implications for limited skills and job options, so they remain dependent on the hereditary profession of fishing. Economically, the average income of the head of a family is only around Rp. 500,000 per month, with a relatively large number of dependents, so it is unable to meet basic needs. In addition, inadequate housing conditions, limited access to clean water that must be brought in from neighboring villages, and uneven lighting further worsen the community's quality of life. From a health perspective, the lack of sanitation and the risks of working as a fisherman also increase vulnerability to poverty. Overall, the characteristics of poverty in the Bajo fishing community in Lamanggau Village are structural and cultural, thus requiring integrated policy interventions to improve education, repair basic infrastructure, and expand economic opportunities for the fishing community.